2018
DOI: 10.1007/jhep05(2018)001
|View full text |Cite
|
Sign up to set email alerts
|

A geometrical upper bound on the inflaton range

Abstract: We argue that in type IIB LVS string models, after including the leading order moduli stabilisation effects, the moduli space for the remaining flat directions is compact due the Calabi-Yau Kähler cone conditions. In cosmological applications, this gives an inflaton field range which is bounded from above, in analogy with recent results from the weak gravity and swampland conjectures. We support our claim by explicitly showing that it holds for all LVS vacua with h 1,1 = 3 obtained from 4-dimensional reflexive… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
96
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(99 citation statements)
references
References 68 publications
(150 reference statements)
3
96
0
Order By: Relevance
“…If it is a pseudo‐scalar like an axion, it can avoid fifth‐force constraints, but a typical axion potential is flat enough to drive a period of accelerated expansion only if its decay constant is trans‐Planckian . This is in disagreement with recent studies of axion field ranges from string theory . On the other hand, if the quintessence field is a scalar, it is not clear how to avoid the existing stringent bounds from fifth‐forces .…”
Section: Quintessence In String Theorymentioning
confidence: 77%
See 1 more Smart Citation
“…If it is a pseudo‐scalar like an axion, it can avoid fifth‐force constraints, but a typical axion potential is flat enough to drive a period of accelerated expansion only if its decay constant is trans‐Planckian . This is in disagreement with recent studies of axion field ranges from string theory . On the other hand, if the quintessence field is a scalar, it is not clear how to avoid the existing stringent bounds from fifth‐forces .…”
Section: Quintessence In String Theorymentioning
confidence: 77%
“…In order to perform a proper study of the implications for quintessence, they have to be considered within a full moduli stabilisation mechanism. However, as mentioned above, one generically needs trans‐Planckian axionic decay constants to drive a period of accelerated expansion while recent studies of axion field ranges in string theory showed that this is very hard to achieve …”
Section: Quintessence In String Theorymentioning
confidence: 99%
“…See also []. for a review related to the distance conjecture, and [] for (an incomplete list of) an analysis of specific inflation models with respect to the distance conjecture.…”
Section: Charting the Swamplandmentioning
confidence: 99%
“…In [] the authors also point out an interesting connection between their refined dS swampland conjecture and the swampland distance conjecture . They do so by using Bousso's covariant entropy bound and thereby provide support for their refined dS swampland conjecture in the asymptotic regime, which is parametrically controlled in a strict, mathematical sense.…”
Section: Introductionmentioning
confidence: 98%